2020
DOI: 10.1016/j.jmmm.2019.165724
|View full text |Cite
|
Sign up to set email alerts
|

Thermal creation of skyrmions in ferromagnetic films with perpendicular anisotropy and Dzyaloshinskii-Moriya interaction

Abstract: We study theoretically, via Monte Carlo simulations on lattices containing up to 1000 × 1000 spins, thermal creation of skyrmion lattices in a 2D ferromagnetic film with perpendicular magnetic anisotropy and Dzyaloshinskii-Moriya interaction. At zero temperature, skyrmions only appear in the magnetization process in the presence of static disorder. Thermal fluctuations violate conservation of the topological charge and reduce the effective magnetic anisotropy that tends to suppress skyrmions. In accordance wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, the defects suppress the skyrmion grown, and the skyrmions are compressed with the average diameter nearly decreasing to a half at x = 5%. At x = 10%, the skyrmion diameters further shrink and are hardly measured due to too high size dispersions and so many nonmagnetic spin vacancies, although the skyrmions can still be identified through Q. Garanin et al [62] using Monte Carlo simulations studied the thermal creation of skyrmion crystals in a 2D ferromagnetic film with perpendicularly magnetic anisotropy and DMI. At zero temperature, the skyrmions only appear in the magnetization process in the presence of static disorder, while the thermal fluctuations violate the conservation of the topological charge and tend to suppress skyrmions through reducing magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the defects suppress the skyrmion grown, and the skyrmions are compressed with the average diameter nearly decreasing to a half at x = 5%. At x = 10%, the skyrmion diameters further shrink and are hardly measured due to too high size dispersions and so many nonmagnetic spin vacancies, although the skyrmions can still be identified through Q. Garanin et al [62] using Monte Carlo simulations studied the thermal creation of skyrmion crystals in a 2D ferromagnetic film with perpendicularly magnetic anisotropy and DMI. At zero temperature, the skyrmions only appear in the magnetization process in the presence of static disorder, while the thermal fluctuations violate the conservation of the topological charge and tend to suppress skyrmions through reducing magnetic anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…Mehmood et al 30 showed that the skyrmion shape can be manipulated by changing the perpendicular magnetic anisotropy. Garanin et al 31 observed a few elliptical skyrmions in a numerical experiment produced by freezing a system of labyrinth domains down to zero temeperature.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, dipole-dipole interaction will be important in systems with centrosymmetry, such as manganites. In case of non-centrosymmetric systems, another anisotropic exchange interaction called Dzyaloshinskii Moriya interaction can also help in stabilization of ferromagnetism/antiferromagnetism in 2D systems 13 . Here, the anisotropy of the system favors a specific spin component which opens a gap in the spin wave spectrum that suppress the effect of thermal fluctuations.…”
Section: Introductionmentioning
confidence: 99%